PERAN ORANG TUA TERHADAP OPTIMALISASI JAJANAN SEHAT PADA TUMBUH KEMBANG ANAK - Siti Aimah; Yuliana Noor Setia Ulvie (Universitas Muhammadiyah Semarang, 2015)
This study was aimed to find out the response of the teachers, parents, food sellers, and students to the effect of danger food for the body. Further, an in-depth research was conducted to find out the extent to which they comprehended the effect of healthy food to the children development. The research used descriptive qualitative. The data were taken from the questionnaire distributed to all subjects of the study by analyzing them in qualitative. The approach used in this research was giving the treatment to the teachers, parents, food sellers, and students to the effect of consuming hazardous food containing toxicity substances. The result was that in pre-observation most of them had not known what kind of toxicity substances containing in any kind of food. They even were not able to differenciate between healthy food and hazardous food. While after being given a treatment, it showed that the response of the teachers, parents, food sellers, and students to the treatment given related to the danger of food for the body performed the result significantly.Keywords: food seller, hazardous food, toxicity substances